2019
DOI: 10.3389/fchem.2019.00653
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Naturally Occurring Phenols and Derivatives Against Biofilm and Planktonic Bacteria

Abstract: Biofilm-forming bacteria present formidable challenges across diverse settings, and there is a need for new antimicrobial agents that are both environmentally acceptable and relatively potent against microorganisms in the biofilm state. The antimicrobial activity of three naturally occurring, low molecular weight, phenols, and their derivatives were evaluated against planktonic and biofilm Staphylococcus epidermidis and Pseudomonas aeruginosa. The structure activity relationships of eugenol, thymol, carvacrol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 96 publications
(127 reference statements)
1
40
1
Order By: Relevance
“…Phenolic compounds are known to damage the bacterial cell wall and inhibit biofilm formation by bacteria. 21 Previous studies revealed molecular interactions between the hydroxyl group of HT and CD in a solid state. 10 , 11 Molecular interactions between the hydroxyl group of HT and CDs as a result of complex formation presumably contributed to the reduced MICs with respect to different bacteria.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Phenolic compounds are known to damage the bacterial cell wall and inhibit biofilm formation by bacteria. 21 Previous studies revealed molecular interactions between the hydroxyl group of HT and CD in a solid state. 10 , 11 Molecular interactions between the hydroxyl group of HT and CDs as a result of complex formation presumably contributed to the reduced MICs with respect to different bacteria.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The search for new bioactive compounds, from the secondary metabolism of plants, that can be used by the pharmaceutical, cosmetic, and food industries has been intensified in the last decade (RODRÍGUEZ-PÉREZ et al, 2015). Among the compounds of greatest interest, phenolic compounds stand out, to which antifungal, antibacterial, antiviral, anti-inflammatory, antiallergic, and cardioprotective activities are attributed, among others (AL-SNAFI, 2019;CÉSPEDES et al, 2008;CHOI et al, 2008CHOI et al, ., 2013ŠAMEC et al, 2010;WALSH et al, 2019;WENG et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For the effective development and application of such novel agents, it is, however, important to have previously compared their efficiency with the classically applied ones. Although several studies have been published in recent years related to the anti-biofilm action of many plant compounds, including CAR, THY and EUG, against various bacteria [33][34][35][36][37], including staphylococci [38][39][40][41], very few of them have compared their actions with those of standard chemical antimicrobials [42][43][44][45][46]. In addition, and to the best of our knowledge, no other study has been published comparing in parallel the efficiency of these three common plant-derived terpenoids (i.e., CAR, THY, and EUG) and of BAC against both planktonic and biofilm Staphylococcus bacteria or of other species.…”
Section: Introductionmentioning
confidence: 99%